Multicultural-Based Islamic Religious Education in Schools - Afifuddin, Afifuddin (Dirasat Islamiah: Jurnal Kajian Keislaman, 2024)
Islamic religious education in schools, particularly in the context of theological instruction, is often delivered with a primary focus on fostering faith and emphasizing the attainment of spiritual rewards such as paradise. However, this approach frequently overlooks the importance of cultivating an awareness of and engagement with other religious traditions. This paper examines the factors contributing to the exclusivist and intolerant tendencies often found in religious education. In an era characterized by globalization and increasing openness, religious education must undergo a paradigmatic and philosophical reorientation. Such an approach should nurture a more inclusive and pluralistic understanding of religion among students, emphasizing multicultural humanism, dialogical persuasion, and active social engagement.